2023
DOI: 10.3390/ijerph20064814
|View full text |Cite
|
Sign up to set email alerts
|

Coping of Chronically-Ill Patients during the COVID-19 Pandemic: Comparison between Four Groups

Abstract: In many countries, the COVID-19 pandemic led to healthcare reorganization limiting access to diagnostic or therapeutic procedures for chronically-ill patients. In this article, we describe the psychological consequences and coping strategies of several groups of chronically-ill patients. During the cross-sectional survey conducted in 2020, we enrolled 398 patients with four different chronic conditions (psoriasis, multiple sclerosis, and patients who have undergone a kidney transplant or received dialysis). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…In this sense, the most resilient people are those who are interested in their vulnerable situations and are receptive to information on how to deal with these situations. Some authors found that problem-focused strategies seem to be very effective in groups of chronically-ill patients during the COVID-19 pandemic [51].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In this sense, the most resilient people are those who are interested in their vulnerable situations and are receptive to information on how to deal with these situations. Some authors found that problem-focused strategies seem to be very effective in groups of chronically-ill patients during the COVID-19 pandemic [51].…”
Section: Practical Implicationsmentioning
confidence: 99%